Contribution of Implementation of ISO 9001:2008 and Principal Leadership on Teacher Performance at SMK Kartini Batam - Yusman Johar (Formosa Journal of Sustainable Research, 2023)
Yusman Johar, Application of constribution ISO 9001:2008 and with Principles of the leadership of teacher’s performance in SMK Kartini Batam. The backround of this researc is about the performance of the teachers in SMK Kartini Batam were low. The implementation of ISO 9001:2008's contribution is the goal of this study and the principle of the leadership of the teacher’s performance. This study included quantitative and correlational methods. that was done found out that 68 teachers only were chosen in sampling random. Data was taken quantitatively using linkert scale to measure the validity and realibility of the data. Hypothesist test was done by using correlation and analysis and regression technic. Analysis result shows that (1) Implementation of ISO constribution 9001:2008 to the teacher’s performance were 0,482 (23,3%). (2) The constribution of principle leadership were 0,488 (23,9%). (3) In conclusion the constribution of implementation ISO 9001:2008 and the principle of leadership toward the teacher’s performance were 0,491 (24,1%). This research was concluded two free variables: Implementation of ISO 9001:2008 and the principle of leadership plays an important rolls in the teachers performance